2011
DOI: 10.1593/neo.101174
|View full text |Cite
|
Sign up to set email alerts
|

Tumors That Acquire Resistance to Low-Dose Metronomic Cyclophosphamide Retain Sensitivity to Maximum Tolerated Dose Cyclophosphamide

Abstract: Low-dose metronomic (LDM) chemotherapy is emerging as an alternative or supplemental dosing strategy to conventional maximum tolerated dose (MTD) chemotherapy. It is characterized primarily, but not exclusively, by antiangiogenic mechanisms of action and the absence of high-grade adverse effects commonly seen with MTD chemotherapy. However, similar to other anticancer therapies, inherent resistance to LDM chemotherapy is common. Moreover, even tumors that initially respond to metronomic regimens eventually dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 46 publications
3
46
0
1
Order By: Relevance
“…Similar results were also found by Klement et al [7]. Nevertheless, in a pre-clinical study, it was demonstrated resistance to MCT, although due to different mechanisms than those involved in resistance to drugs administered in the maximum tolerated dose (MTD) [8].…”
Section: Introductionsupporting
confidence: 80%
“…Similar results were also found by Klement et al [7]. Nevertheless, in a pre-clinical study, it was demonstrated resistance to MCT, although due to different mechanisms than those involved in resistance to drugs administered in the maximum tolerated dose (MTD) [8].…”
Section: Introductionsupporting
confidence: 80%
“…Resistance to metronomic CPA has been associated with dormant stem-cell foci in hepatocellular carcinoma [51], ischemia-dependent K-ras mutations in colorectal carcinoma [52] and increased annexin A3 expression in prostate cancer [53; 54]. Different resistance mechanisms may be activated in different tumor models and by different CPA doses and schedules [55; 56]; these mechanisms could include immune-based resistance, as well as repopulation of quiescent tumor cells that are distal of blood vessel and deprived of oxygen and nutrients, selection of tumor cell populations with increased drug efflux and detoxification ability, increased DNA damage repair between metronomic CPA treatments, metabolic adaptation, and emergence of resistance to apoptosis [57; 58]. In preliminary studies of regressing GL261 tumors, we have seen ~2-fold higher expression of ALDH1A1 six days after two CPA injections on the CPA/9d compared to the CPA/6d schedule (unpublished results); ALDH1A1 inactivates CPA-derived aldophosphamide and can confer CPA resistance [59].…”
Section: Discussionmentioning
confidence: 99%
“…In this view, the use of CXB may have contributed both to a significant reduction of chemotherapy toxicity, such as haematological ones [33], and to the control of pain related to the disease. Moreover, a recent article by Emmenegger and colleagues [34] suggests that resistance to metronomic cyclophosphamide is a distinct phenomenon from resistance to maximum tolerated dose (MTD) cyclophosphamide and that metronomic cyclophosphamide administration does not select for MTD chemotherapy resistance. These findings, together with our data, may suggest to start metronomic cyclophosphamide earlier than previously thought, especially in a subset group such as frail and elderly patients, because of the open possibility to further treat these patients with MTD cyclophosphamide schedules without harming a possible response.…”
Section: Discussionmentioning
confidence: 99%